Antecedents of organizational citizenship behavior among Turkish white-collar employees in The Netherlands and Turkey. (November 2015) - Ersoy, Nevra Cem; Derous, Eva; Born, Marise Ph.; van der Molen, Henk T.
Abstract: This study examined antecedents of organizational citizenship behavior (i.e., reward for application; religiosity beliefs and employees' relational identification with their supervisor) among Turkish white-collar employees in The Netherlands ( n  = 103) and Turkey ( n  = 147). OCB related positively to reward for application (both samples) but not to religiosity beliefs among Turkish employees in their home country (Turkey). As expected, relational identification with the supervisor was less strongly related to organizational citizenship behavior among Turkish white-collar employees in their host country (The Netherlands) compared to their home country (Turkey), especially when they resided longer in their host country. Giving increasing globalization and war for talent, findings are relevant to better understand effects of white-collar migrants' cultural background and acculturation patterns in work-related domains, like OCB.